Back Cover: Insights into Deactivation and Regeneration of an Industrial Cu/Ni/Cr‐Al2O3 Catalyst During Aldehyde Hydrogenation (ChemCatChem 23/2016). Issue 23 (7th December 2016) - Reinsdorf, Arne; Korth, Wolfgang; Jess, Andreas; Terock, Michael; Klasovsky, Florian; Franke, Robert
Abstract : The Cover shows the steps that were followed to investigate the deactivation of a commercial hydrogenation catalyst, using n ‐nonyl‐aldehyde as model reactant. Mainly aromatic fractions were identified in the carbonaceous residues from the spent plant catalyst.In their Full Paper, A. Reinsdorf et al. offer a novel insight into the hydrogenation of oxo‐aldehyde. The deactivation of commercial hydrogenation catalyst was investigated in detail, showing how aldehyde‐aldol side reactions lead to high molecular compounds that strongly adsorb on the catalyst's inner surface. More information can be found in the Full Paper by A. Reinsdorf et al. onpage 3592 in Issue 23, 2016 (DOI:10.1002/cctc.201601022 ).